Bulgarian general population attitude to mandatory COVID-19 vaccination: A nationwide cross-sectional study - Rouzha Pancheva; Rositsa Chamova; Maria Rohova; Nikolay Mihaylov; Stanislava Hadzhieva; Miglena Kolarova; Eliyana Ivanova; Nikolina Radeva; Tsonko Paunov; Adamos Hadjipanayis (Elsevier, 2023)
Background: The issue of mandatory COVID-19 vaccination, entwined with citizens' rights and autonomy, impacts vaccine uptake and trust in health authorities. This study centers on Bulgaria, aiming to uncover attitudes towards obligatory COVID-19 vaccination. Methods: Employing an online questionnaire, we conducted a cross-sectional survey involving 1433 adults in Bulgaria between April and May 2022. Analysis of responses from 1200 participants illuminated perspectives on mandatory COVID-19 vaccination. Results: Among respondents, 38.6% supported or were uncertain about mandatory vaccination, while 61.4% opposed it. Binary logistic regression, utilizing demographic predictors, unveiled that younger age groups, particularly those aged 18-25, demonstrated diminished odds of supporting mandatory vaccination. Those with apprehensions about contracting the virus (OR 2.98, 95% CI 1.65-5.39), perceiving minimal vaccine risks (OR 3.86, 95% CI 1.80-8.26), acknowledging vaccine benefits for health protection (OR 3.86, 95% CI 1.80-8.26), and pandemic containment (OR 3.34, 95% CI 1.16-9.60) were more prone to endorse mandatory vaccination. Trust in general practitioners and pharmaceutical companies also emerged as influential factors. Conclusion: The study portrays a diverse sentiment within Bulgaria's population concerning compulsory COVID-19 vaccination. It underscores the importance of conveying accurate, evidence-based information while upholding individual autonomy. National health authorities should harmonize methodical vaccination initiatives with health promotion interventions targeted at the general population and healthcare professionals. Such an approach can facilitate well-informed choices and contribute to public health objectives.